PEMBUATAN LAPISAN FOTOKATALIS ZINC OXIDE (ZnO) DENGAN TEKNIK SPRAY COATING DAN APLIKASINYA PADA PENGERING JAGUNG - Hidayanto, Eko; Sutanto, Heri; Firdausi, K Sofjan; Arifin, Zaenal (BERKALA FISIKA, 2013)
ZnO thin film has been deposited on the glass with a spray coating technique. Gel of ZnO 0.5 M was synthesized by dissolving 0.5 M zinc acetate dehydrate in isopropanol andmonoethanolamine solution at room temperature with the molar ratio of MEA and ZnAc is 1:1. The solution was stirred using a magnetic stirrer at 70°C for 30 minutes to get the clear and homogeneous ZnO gel. ZnO gel is placed on the spray hole and sprayed on a heated glasssubstrate till 40oC. Then, the spraying layer spraying was allowed to stand for 3 days tostrengthen the contact with glass layer. Deposition results of ZnO layer is transparent withtransmittance values of 71.4 % and decreases with a decrease in wavelength imposed on the layer.The energy dispersive X-ray (EDX) results show the composition of zinc (Zn) is less than theoxygen (O) with a ratio Zn : O = 38.44 % : 61.56 %. The scanning electron microscopy (SEM)results show ZnO thin film has a smooth and homogeneous surface with a grain size of 57 nm. Thetest results demonstrate ZnO layer has a band gap value of 3.01 eV. The drying corn shows thatdirectly drying using sunlight has a faster rate compared using ZnO glass. Surface morphology ofthe layer of dried corn using ZnO glass has brighter color and lice compared to directly drying onsunlight.Keywords: Photocatalyst, ZnO, Thin Film, Spray Coating, Corn, Drying